Clinical management of children with tic disorder: insights from therapeutic visits in China—a real-world study - Wang, Jing; Luo, Changyong; Wang, Zhendong; Liu, Tiegang; Bai, Chen; Wang, Yang; Tian, Yuanshuo; Li, Qianqian; Wang, Zhaoxin; Wu, Liqun; Wang, Sumei; Gu, Xiaohong (Frontiers in Pediatrics, 2024)
Objective: This retrospective study aims to investigate the treatment of tic disorder (TD) in Dongfang Hospital affiliated with Beijing University of Chinese Medicine, explore its underlying mechanism, and provide valuable insights for future research and clinical management of TD.Methods: Electronic medical records of children with TD from 2015 to 2021 were extracted from the information system of Dongfang Hospital affiliated with Beijing University of Chinese Medicine. The clinical characteristics of TD, utilization patterns of Chinese herbal medicine and synthetic drugs in prescriptions, as well as their pharmacological effects, were statistically described and categorized.Additionally, association rules and network pharmacology were employed to identify core prescriptions (CP) and elucidate their microscopic molecular mechanisms in treating TD.The age range of the children was 6 to 11 years, with a higher proportion of male participants than female ones. The average duration of treatment was 6 weeks.The treatment regimen Z for TD was summarized as: Chinese herbal medicine (Saposhnikoviae Radix (FangFeng), Puerariae Lobatae Radix (GeGen), Uncariae Ramulus cum uncis (GouTeng), Acori Tatarinowii Rhizoma (ShiChangPu), Chuanxiong Rhizoma (ChuanXiong), etc. and vitamins (Lysine Inosite and Vitamin B12 Oral Solution, etc.) as the basic treatment, combinated with Immunomodulator, Antibiotics, Electrolyte Balancing Agents, Antiallergic Agents. CP primarily exerted its effects through modulation of gene expression (transcription), the immune system, and the signal transduction pathways, particularly Interleukin-4 and interleukin-13 pathways being crucial.Among Lysine synthetic drugs used, Inosite and Vitamin B12 Oral Solution were the most frequently prescribed .The drug treatment Regimen Z holds significant importance in the field, which exerted therapeutic effects through a multitude of pathways and intricate 3 interventions. Chinese herbal medicine primarily regulated immune system-related pathways, while synthetic drugs predominantly consisted of vitamins.